The Quebec City Slider: A Technique for Capsular Closure and Plication in Hip Arthroscopy - Menge, Travis J. (Arthrosc Tech, 2016)
Biomechanical and clinical studies have shown that the hip joint capsule plays an important role in maintaining stability and hip mechanics, including rotation and translation. The recent literature has shown that capsule closure after hip arthroscopy helps to restore stability. Without restoration of the native anatomy, the hip joint may translate when patients engage in activities that place force across the hip, leading to either microinstability or frank dislocation. The purpose of this note is to describe our preferred technique of capsular closure or plication during hip arthroscopy.